(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The first and fundamental approach to classify the sounds according to the phonetic characteristics is by the source of the airflow. The languages of the world use many types of airstream mechanisms to create their sounds, the most known mechanisms are: Pulmonic, Glottalic and velaric airstream mechanisms. In English sound system, for instance, all sounds are created by airstream mechanism made by the expiration of the airflow from the lungs, and this process is known as (Pulmonic Airstream Mechanism). The expression ’airstream mechanism’ has several concepts and significations. In modern discussion, airstream mechanisms are understood as airflow production in the larynx area influenced by the vocalic and consonant segment. In general, the respiratory airstream mechanisms are regarded as physiological phenomena.